Purchase Preference Of Selected Malaysian Motorcycle Buyers: The Discriminating Role Of Perception Of Country Of Origin Of Brand And Ethnocentrism - Neoh , Chee Yeong; Mohamad, Osman; T. Ramayah, T. Ramayah; Omar, Azizah (Asian Academy of Management (AAM), 2007)
The influence of country of origin on the evaluation of products and purchase intention has been studied for decades. However, this paradigm has shifted where nowadays, products are typically designed in one country, manufactured in another and assembled elsewhere which led to the proliferation of "hybrid products". Consumers are confused and are no longer able to identify or recognize the difference between country of origin of brand and country of assembly or country of product design which, in turn, may lead to wrong purchasing decisions. The objective of this study is to understand the variables influencing consumers' purchase preference related to motorcycles in the Malaysian market. Results have confirmed that country of origin of brand and consumer ethnocentrism influence consumer purchase preference. Implications of the results and directions for future researches are also discussed.